Pembaharuan Pendidikan Islam Studi Pemikiran Fazlur Rahman Tentang Konsep Pendidikan Tinggi Islam - Hujair AH. Sanaky (Islamic University of Indonesia, 2002)
This article traces that the essence of Islamic education, according Fazlur Rahman, does not only refer to the material equipments for instance the text books, that were taught or external structure of education but it teas also according to Rahman that aimed of Islamic Education was